Contribution to the Trichoptera fauna of the river La Vieja, Bogotá, Colombia (Insecta: Trichoptera) - Mey, Wolfram; Ospina-Torres, Rodulfo (Zootaxa, 2018)
Investigation of the Trichoptera fauna from the small river La Vieja on the city border of Bogotá yielded a total of 17 species. Nine new species of Trichoptera are described from La Vieja: Atopsyche viejae spec. nov., A. flavoantennata spec. nov., Metrichia trisignata spec. nov., M. longiphallata spec. nov., Smicridea colombosaucia spec. nov., Xiphocentron laviejae spec. nov., Phylloicus monserratensis spec. nov., Marilia bogotaensis spec. nov., and Oecetis chapinera spec. nov. Images of the adults of some species are provided, and the male genitalia are illustrated. The genitalia of three additional species (Hydroptila constricta Bueno-Soria 1984, Polycentropus joergenseni Ulmer 1909, Contulma spec.) are depicted to facilitate their future identifications.